LORD BYRON’S LOVE AFFAIRS AS REFLECTED IN HIS POETRY = LORD BYRON: TÌNH YÊU VÀ THƠ CA - Ngô, Hạnh Quyên (2020)
Lord Byron was one of the greatest poets in Romanticism. He was famous for both his notorious love life and outstanding poetry. For Byron, poetry was the reflection of love which, in turn, was the root of poetry. This research will be based on the strong connection between these inseparable factors to study Byron’s emotions when he was in his relationships with Mary Chaworth, John Edleston, Augusta Leigh, Lady Byron, and Countess Teresa Guiccioli, by analysing literary language in some related poems of the Poet. The research will then find out the characteristics of these love affairs, as well as the differences among them, so as to highlight Byron’s characteristics in love.